Molecular priming as an approach to induce tolerance against abiotic and oxidative stresses in crop plants - Kerchev, Pavel; van der Meer, Tom; Sujeeth, Neerakkal; Verlee, Arno; Stevens, Christian V; Van Breusegem, Frank; Gechev, Tsanko (Biotechnology advances, 2020)
Abiotic stresses, including drought, salinity, extreme temperature, and pollutants, are the main cause of crop losses worldwide. Novel climate-adapted crops and stress tolerance-enhancing compounds are increasingly needed to counteract the negative effects of unfavorable stressful environments. A number of natural products and synthetic chemicals can protect model and crop plants against abiotic stresses through induction of molecular and physiological defense mechanisms, a process known as molecular priming. In addition to their stress-protective effect, some of these compounds can also stimulate plant growth. Here, we provide an overview of the known physiological and molecular mechanisms that induce molecular priming, together with a survey of the approaches aimed to discover and functionally study new stress-alleviating chemicals.
Keywords: Stress, Physiological; Plant Development; Droughts; oxidační stres; salinita; Hydrogen peroxide; vývoj rostlin; fyziologický stres; Oxidative Stress; Salinity; období sucha; Biostimulants; Molecular priming